Associations between non-insulin-based insulin resistance surrogate markers and liver-related outcomes in metabolic dysfunction-associated steatotic liver disease: a nationwide cohort study in South Korea - Sang Yi Moon; Minkook Son; Yeo Wool Kang; Myeongseok Koh; Jong Yoon Lee; Yang Hyun Baek (BMC Gastroenterology)
Abstract Background Insulin resistance (IR) is a crucial mechanism in the pathogenesis and clinical progression of metabolic dysfunction-associated steatotic liver disease (MASLD). This study aimed to examine the relationship between non-insulin-based IR surrogate markers and the incidence of liver-related outcomes in individuals with MASLD in a nationwide Korean cohort. Methods A total of 66,334 individuals with MASLD who underwent a health examination between 1 January 2009 and 31 December 2010 were included in the study and followed until 31 December 2019, with a median follow-up period of 9.4 years. Hepatic steatosis was defined as a fatty liver index ≥ 30. The triglyceride-glucose (TyG) index, triglyceride-to-high-density lipoprotein cholesterol (TG/HDL) ratio, and metabolic score of IR (METS-IR) were employed as non-insulin-based IR surrogate markers. The MASLD groups were divided into four groups based on the non-insulin-based IR surrogate markers quartiles. The primary outcome was liver-related outcomes, as a composite of hepatocellular carcinoma and decompensated liver cirrhosis. Results The MASLD group was 64.4% male (average age, 59.0 years). Using the lowest quartile (Q1) of the three non-insulin-based IR surrogate markers as a reference, a decrease in the adjusted hazard ratio for liver-related outcomes was observed from Q2 to Q4: (TyG: Q2 0.90 [95% confidence interval [CI]: 0.79–1.02], Q3 0.80 [95% CI: 0.70–0.91], Q4 0.80 [95% CI: 0.69–0.92]; TG/HDL: Q2 0.85 [95% CI: 0.75–0.97], Q3 0.81 [95% CI: 0.71–0.92], Q4 0.81 [95% CI: 0.71–0.93]; METS-IR: Q2 0.83 [95% CI: 0.73–0.95], Q3 0.80 [95% CI: 0.70–0.91], Q4 0.80 [95% CI: 0.70–0.92]). Conclusions A lower non-insulin-based IR surrogate marker in the MASLD group may be associated with an increased risk of liver-related outcomes. In the course of monitoring MASLD, metabolic alterations must be meticulously observed.